2021
DOI: 10.1108/sej-03-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between social enterprises and key actors shaping the field: experiences from the social and health sectors in Hungary

Abstract: Purpose In Hungary, as in other Central and Eastern European countries, the concept of social enterprise (SE) has attracted increased attention in recent years, with certain key actors shaping the organisational field. This growing interest is largely because of the availability of European Union funds focussing on the work integration of disadvantaged groups but ignoring other possible roles of SEs. This study aims to consider a seldom examined and underfunded area: SEs’ institutional environment and organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Based on the international development trend, in facing obstacles to the development of social enterprises, it is a trend for governments to promote the development of social enterprises through public policies [ 77 ]. The support of central and local governments to social enterprises has been paid more and more attention [ 26 , 78 ]. Institutions constrain the development of social enterprises [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the international development trend, in facing obstacles to the development of social enterprises, it is a trend for governments to promote the development of social enterprises through public policies [ 77 ]. The support of central and local governments to social enterprises has been paid more and more attention [ 26 , 78 ]. Institutions constrain the development of social enterprises [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2017). Similarly, Kiss et al. (2021) found that SEs in the social and health sectors in Hungary that substitute public institutions as a result of the state’s withdrawal from welfare services primarily depend on funding from central state budgets, public social and health institutions, local governments and EU cofinanced grants.…”
Section: Hungarian Context Of Social Enterprisesmentioning
confidence: 96%
“…Most Central and Eastern European SEs cannot achieve economic sustainability exclusively through their business revenue, thus they require donations, grants and volunteer work (G. Fekete et al, 2017) estimations regarding the extent of external financial support range from 25% (SEFORIS research consortium, 2016) to 52% (G. Fekete et al, 2017). Similarly, Kiss et al (2021) found that SEs in the social and health sectors in Hungary that substitute public institutions as a result of the state's withdrawal from welfare services primarily depend on funding from central state budgets, public social and health institutions, local governments and EU cofinanced grants.…”
Section: Dual Commitment Of Social Enterprisesmentioning
confidence: 97%
“…Moreover, political, legal, and economic conditions influence social enterprises (MacDonald and Howorth 2018). Governments impact the everyday operation of social enterprises through legislation and funding support (Kiss et al 2021). In this regard, policy strategies should address social innovation initiatives to overcome market failure and deliver social good.…”
Section: Theoretical Foundationmentioning
confidence: 99%